2022
DOI: 10.3389/fendo.2022.817176
|View full text |Cite
|
Sign up to set email alerts
|

Elevated TyG Index Predicts Incidence of Contrast-Induced Nephropathy: A Retrospective Cohort Study in NSTE-ACS Patients Implanted With DESs

Abstract: BackgroundTriglyceride-glucose (TyG) index is a reliable and specific biomarker for insulin resistance and is associated with renal dysfunction. The present study sought to explore the relationship between TyG index and the incidence of contrast-induced nephropathy (CIN) in non-ST elevation acute coronary syndrome (NSTE-ACS) patients implanted with drug-eluting stents (DESs).MethodsA total of 1108 participants were recruited to the study and assigned to two groups based on occurrence of CIN. TyG index was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…Interestingly, the result strengthened the association between the high TyG index (TyG > 8.72) and the renal outcome of IgAN. Consistent with these findings, previous epidemiologic studies have identified that TyG is positively connected with deterioration of renal function in diabetic nephropathy [ 24 ] and contrast-induced nephropathy [ 11 ], but no relevant literature confirms and compares a significant correlation between TyG indices and IgAN thus far.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Interestingly, the result strengthened the association between the high TyG index (TyG > 8.72) and the renal outcome of IgAN. Consistent with these findings, previous epidemiologic studies have identified that TyG is positively connected with deterioration of renal function in diabetic nephropathy [ 24 ] and contrast-induced nephropathy [ 11 ], but no relevant literature confirms and compares a significant correlation between TyG indices and IgAN thus far.…”
Section: Discussionmentioning
confidence: 56%
“…It has shown the advantages of being more convenient and easily accessible in clinical practice than plasma insulin in the homeostasis model assessment of IR [ 7 ]. Epidemiological and basic science studies have shown that the elevation of the TyG index correlates well with atherosclerosis, cardiovascular risk, progression of chronic kidney disease (CKD), and renal dysfunction [ 3 , 8 , 9 , 10 , 11 , 12 ], all of which are prevalent all over the world. A previous study showed that glucose metabolism and dyslipidemia were common in IgAN patients, and IR seemed to be associated with the development of kidney dysfunction in IgAN [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 36 38 ] A recent study showed that; elevated TyG Index associated with CIN in NSTE-ACS patients implanted with DESs. [ 39 ] In contrast to our study, this study includes only diabetic and stent implanted patients. Furthermore, our study includes all non-diabetic patients who underwent angiography and shows the correlation between CIN and TyG index in non-diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The TyG index is derived from TG and FBG levels, and is a reliable surrogate IR marker. Thus, TyG is becoming a promising alternative indicator of IR due to its e cacy, simplicity, and low cost [12,15,25] . Studies have shown that the TyG index was highly sensitive (96.5%) and speci c (85.0%) for the detection of IR, compared to the hyperinsulinemiceuglycemic clamp technique [12] .…”
Section: Discussionmentioning
confidence: 99%